2022
DOI: 10.1177/1356336x221106051
|View full text |Cite
|
Sign up to set email alerts
|

Middle school students’ attitudes toward physical activity and physical education, intentions, and physical activity behavior

Abstract: Schools are focusing more on promoting physical activity (PA) before, during, and after the school day, to combat the risk factors associated with sedentary behaviors. Since attitudes impact decisions to be physically active, identifying how PA attitudes relate to established attitudes toward physical education (PE), as well as PA intentions and behaviors are important—and thus the focus of this study. Middle school students ( N = 948; 45% female) completed PA behavior, PA intention, and PA and PE attitude sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 41 publications
2
8
0
Order By: Relevance
“…The change in attitude toward physical exercise will stimulate the development of health-related behaviors (e.g., regular sleep and eating, controlled smoking, and drinking). The result is consistent with previous research [ 56 , 57 ], in which people with positive attitudes toward physical exercise tended to be more disciplined and had fewer unhealthy behaviors. In short, maintaining a positive attitude toward physical exercise is of great significance in cultivating awareness of health-related behaviors.…”
Section: Discussionsupporting
confidence: 92%
“…The change in attitude toward physical exercise will stimulate the development of health-related behaviors (e.g., regular sleep and eating, controlled smoking, and drinking). The result is consistent with previous research [ 56 , 57 ], in which people with positive attitudes toward physical exercise tended to be more disciplined and had fewer unhealthy behaviors. In short, maintaining a positive attitude toward physical exercise is of great significance in cultivating awareness of health-related behaviors.…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of overweight or obese children and adolescents aged 5–19 years, has surged from 4% in 1975 to an alarming 18% in 2016 ( 7 ). To mitigate or forestall obesity, precautionary measures, such as fostering a positive disposition toward physical activity, should be implemented for children and adolescents ( 46 ). In this context, the primary objective of this investigation was to scrutinize the correlation between attitudes towards physical activity and weight gain among students in elementary and middle schools.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, in the domain of negative attitudes, students at the age of 9 scored higher than their peers in other age categories. An analogous study, albeit with a different focus, conducted by Mercier et al ( 46 ), examined variations in attitudes towards physical activity with respect to grade levels. Their findings revealed that 6th-grade students exhibited a more favorable positive attitude and a less pronounced negative attitude compared to 7th and 8th-grade students.…”
Section: Discussionmentioning
confidence: 99%
“…Through the intentional construction of positive challenges using physical literacy in PE, participants also suggested this supported student engagement, motivation, and continued participation within their PE classes. Ultimately, given repeated provision of positive movement experiences in the PE context, this could lead to the association of happiness with physical activity as students emerge into adulthood ( 9 , 32 ). The combination of these pedagogical practices over the course of a PE program supports the activation of the physical literacy cycle and the various feedback pathways, in a variety of different movement and social contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Shifting away from the dehumanizing physical activity promotion strategies to support intrinsic valuation of movement ( 6 ), as exemplified in physical literacy through concurrent development of competence and psychological characteristics such as confidence and motivation ( 7 ), may be a way to support more sustainable behaviour change. One of the contexts in which this shift in thinking may be particularly impactful is in schools where positive movement experiences can be supported ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%